PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI SAINS SISWA - Pasiri, Yuddin (Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to determine the influence of the Problem Based Learning model on the scientific literacy abilities of class IV students at SD Negeri Tetebatu 1 Kabupaten Gowa Regency. This research uses quantitative research methods using True- experimental. The population in this study were all class IV students, the sample with a total of 28 students. The sampling method in this research used a saturated sampling technique. The results of the research show that the average score obtained by students in the pre-test class IV 76.15 which was in the sufficient category and the average score obtained by students in the post-test score in Class IV was 88.08 which was in the category Good. The results show that the use of the Problem Based Learning model can improve the scientific literacy skills of class IV. The results of data analysis obtained a sig value. 0,000. It turns out that the sig value. 0.000 is smaller than the probability value of 0.05 or in other words the value 0.05 > 0.000. So it can be concluded that, there is an influence of the Problem Based Learning model on the scientific literacy abilities of class IV at SD Negeri Tetebatu 1 Kab. Gowa Regency.